In vitro flowering of selected ornamental plants - Mat Taha, R.; Hasbullah, N.A.; Awal, A. (2009)
In vitro flowering of three selected ornamental species from Malaysia was studied. Oxalis triangularis, Celosia cristata and Begonia x hiemalis were found to be able to flower on MS Murashige and Skoog, 1962) medium supplemented with various hormones, such as Benzyl aminopurine (BAP), Naphthalene acetic acid ( NAA), etc at different concentrations. In tissue culture, in vitro flowering is normally induced for many reasons. One of the most important ones being to shorten the life cycles of plants, other aims include to gather knowledge on in vitro flowered plantlets for the formation of fruits and seeds, to overcome problems associated with premature fruit drop or poor seed set. In the present work, we focused on the effect of different hormones and concentrations, on in vitro flowering of the three selected species. The effect of Adenine and sucrose at different concentrations were also tested for Begonia x hiemalis.